Providing business support to SMEs – how to encourage firms’ engagement - Braidford, Paul; Stone, Ian (Journal of Public Governance, 2016)
Objectives. While most governments operate a support system for SMEs aiming to encourage improved business performance, there is a widespread problem of having such firms engage with schemes of this kind. This policy issue is tackled here through work to develop a better understanding of SMEs’ attitudes towards the accessing and use of support programmes with a view to their business objectives being achieved. A typology of SMEs based on past interactions with the support system is identified, and consideration given to the way in which this inf luences their attitude to public (and private) support; as well as the way in which the recession has affected use and attitudes.Prior Work. Prior work has concentrated on models relating the propensity to use support to business and owner characteristics (Han and Benson, 2009), growth strategies (Johnson & Webber, 2007) or delivery mechanisms (Mole, Hart and Roper, 2014); or simply to a desire to solve a problem (Mole and Keogh, 2009). Targeting support on this basis is difficult.Approach. 100 in-depth, semi-structured face-to-face interviews were conducted across England with users of schemes delivered by one or more of four publicly-funded support services (UKTI, MAS, GrowthAccelerator and TSB). Questions were based around progression of usage on a customer journey (rationale for using support, awareness of schemes, investigation, application, use of the service) and attitude formation through contact with support schemes, network contacts, etc.Results. Four different types of user were identified by reference to experience with and use of support, reasons for use and attitude towards future use. These were: (i) experienced and sophisticated consumers of support; (ii) experienced users, but with a more narrow, transactional-focused outlook; (iii) returning/lapsed users, who had often not used support since before the recession or since their establishment; and (iv) inexperienced users, many of whom were accessing support for the first time. Common across all types were (i) the identification of a lack of a common entry point for support or diagnostic advice; (ii) a low level of investigation into support available before the service was approached; and (iii) a low level of cross-referral between services during or after support.Implications. The use of evidence based on attitudes and rationales, rather than owner/business characteristics, allows for a more nuanced analysis of the behaviour of businesses in seeking and using business support. In particular, it facilitates an understanding of how businesses see support schemes working together to cover potential needs.Value. Achievement of an optimal use of support through engagement of firms entails a recognition that the process involved is of importance. The identification of different types of user, and of differences and similarities in the use they make of support, allows for better targeting of support and design of delivery, thereby facilitating tailoring in regard to the way in which businesses become aware of, and make use of, support. The aim is to better inform the approach to and delivery of SME support schemes, in order that take-up and effectiveness can be improved. Although the paper is based upon a UK case study, its findings have broader policy relevance, especially given a widespread trend towards the provision of support online, rather than by more direct methods. The research shows that firmsseem to require bespoke advice (i.e. information, diagnosis and brokerage), and that this plays an inf luential ‘gateway’ role encouraging firms to engage with support organisations.